Immunologic defects in leprosy patients. II. Interleukin 1, interleukin 2, and interferon production in leprosy patients - Makonkawkeyoon S. (2014)
The capabilities of monocytes and lymphocytes in peripheral blood mononuclear leukocytes (PBML) to produce interleukin-1 (IL-1), IL-2, and interferon (IFN), respectively, were evaluated in various types and treatments of leprosy patients. IL-1 production in response to lipopolysaccharide was significantly lower in LL, BL, BB, and BT patients than in normal controls. However, there were no differences in IL-1 levels between TT patients and normal controls. The percentages of nonspecific-esterase-positive cells adhering to the plastic surfaces were not different in LL, BB and TT patients when compared to normal controls. However, they were significantly higher in BT and BL patients than in normal controls. When PBML from leprosy patients were stimulated with concanavalin-A (ConA) for IL-2 production, there were no differences in the IL-2 levels in treated BL/LL, untreated BL/LL, treated BT/TT, and untreated BT/TT patients compared to normal controls. Similar results were obtained when PBML were stimulated with phytohemagglutinin-P (PHA-P). However, when purified protein derivative (PPD) was used as the stimulating agent, there were significantly lower IL-2 levels in treated BL/LL, untreated BL/LL, treated BT/TT, and untreated BT/TT patients when compared to normal controls. There were also lower IL-2 levels in untreated BL/LL and BT/TT patients compared to treated BL/LL and BT/TT patients, respectively. PBML were stimulated with PHA-P or ConA for IFN production.(ABSTRACT TRUNCATED AT 250 WORDS)